ХИРУРГИЧЕСКОЕ ЛЕЧЕНИЕ ОСТЕОХОНДРОЗА ПОЯСНИЧНОГО ОТДЕЛА ПОЗВОНОЧНИКА: СОВРЕМЕННЫЕ ПОДХОДЫ И КЛИНИКО-НЕВРОЛОГИЧЕСКИЕ КОРРЕЛЯЦИИ. (Multidisciplinary Journal of Science and Technology, 2025)
The article presents an analysis of modern surgical approaches to lumbar spine osteochondrosis based on clinical and neurological characteristics. A total of 148 patients who underwent different surgical procedures—microdiscectomy, endoscopic discectomy, laminectomy, and TLIF/PLIF—were evaluated. Pain dynamics (VAS), neurological symptom regression, and functional status (ODI) were assessed. The findings indicate that TLIF/PLIF provides the best outcomes in patients with segmental instability, while endoscopic discectomy demonstrates the lowest surgical invasiveness. Microdiscectomy remains highly effective with minimal complication rates. The results align with current international guidelines and emphasize the importance of individualized selection of surgical strategy.